PENINGKATKAN HASIL BELAJAR SISWA MELALUI METODE INKUIRI MATA PELAJARAN PKN KELAS IV SD NEGERI 164525 KOTATEBING TINGGI - Nurmala Simanjuntak (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2018)
This purposes of this research is to improve learning result on PKn subject  through Inquiry method. This classroom action research conducted by 3 cycles of the four phases: planning, implementation, observation, reflection. The subjects were students from class IV, SD N 164525 Tebing Tinggi which amounted to 33 students. This study used a qualitative descriptive analysis technique. The results showed that the use of the inquiry method of PKn subjects can improve student learning result characterized by increased mastery learning students, namely pre-cycle (51,51%), the first cycle (57,57%), cycle II (81,81%), the third cycle (90,90 %) and complete learn the clasical equal to 90,90 %.Keywords : Inquiry, learning result, PKN